A sujeição passiva e a responsabilidade tributária dos sucessores no Código Tributário Nacional - Henrique, Márcio Alexandre Ioti (2009)
The passive subjection and the tax liability are controversial topics that the legal writing and the Brazilian court decisions are not unanimous. In this work, it is done an analysis of these legal institutes, focusing specifically the successor tax liability, ruled in the articles 130 to 133 of the Brazilian Tax Code. There is no doubt that the analysis of these legal institutes must begin in the constitutional text. So, after analyzing constitutional text, it is possible to assure that it rules who is able to be in the passive subject of the tax legal relationship. This is the first relevant point that shall be verified. It is also possible to verify that regarding the liability statutes ruled in Brazilian Tax Code, none of them has a really tax nature. In fact, the statutes causes the appearance of an administrative legal relationship, that may have or not a penalty characteristic, depending on the sort of liability that is being discussed. That is the reason why it is possible to affirm that the tax liable shall not be confused with the passive subject of the tax legal relationship. Specifically regarding the successor tax liability statutes, it is possible to verify that they are species with no penalty characteristics and they may occur in an inter vivos or causa mortis acts. They do not have a penalty characteristic, because all the species of successor tax liability results of an lawful act, completely allowed in the national legal system. This shall be the defended positioning in this work, which in a critical way, shall force a better contemplation about the legal institutes studied